A Study on the Determinants of Employee Engagement Among Generation Z in the Manufacturing Sector of Semarang Regency - Yetiria Zega; Dyah Palupiningtyas (International Journal of Economics and Management Research, 2025)
This study aims to analyze the factors influencing employee engagement among Generation Z in the manufacturing industry in Semarang Regency. Using a qualitative approach with case study design, data were collected through in-depth interviews, focus group discussions, participatory observation, and document analysis involving 25 Generation Z employees from three manufacturing companies. The results identified five main factors affecting employee engagement: job design and autonomy, leadership and supervisor relationships, career development and continuous learning, work environment and organizational culture, and work-life balance and flexibility. Career development and continuous learning emerged as the most influential factor (84.7%), followed by leadership and supervisor relationships (81.2%). Companies that successfully engage Generation Z employees are those that balance manufacturing standardization requirements with Generation Z's preferences for autonomy, self-development, and flexibility. The findings contribute to enriching the understanding of employee engagement in the specific context of Generation Z in the manufacturing industry and provide practical guidance for manufacturing companies in developing more effective human resource management strategies. This research suggests that manufacturing companies need to transform their approach to human resource management to accommodate the unique preferences and expectations of Generation Z.